Diagnostic Performance of Kato Katz and Point of Care Circulating Cathodic Antigen Assays for Detection of Schistosoma Mansoni and their Utility in Monitoring Preventive Chemotherapy in Siaya County, Western Kenya - Njuhi, Geoffrey Muchiri (JOOUST, 2024)
Schistosomiasis pauses a serious public health concern, causing significant morbidity and mortality in tropical countries, despite there being affordable, effective, and safe drugs for its treatment. Accuracy in detection of the disease in endemic and at-risk populations is important to achieve elimination goals in line with WHO NTD 2030 roadmap. Kato- Katz assay has historically remained reliable assay for the diagnosis of schistosomiasis and most intestinal parasites, but it has major drawbacks, including low sensitivity and the need to promptly process stool samples upon collection. The novel point of care circulating cathodic antigen (POC-CCA) test using urine has shown promise for the detection of S. mansoni in different settings, and thus a growing need for its validation and utility in monitoring and evaluation of control programs for S. mansoni. This study evaluated the diagnostic performance of Kato Katz and POC-CCA in the detection of S. mansoni infections in low and high prevalence areas and to determine their effectiveness in monitoring of preventive chemotherapy, using a repeated cross-sectional approach, where 329 school-aged children (9-12 years) were enrolled each year and provided single stool and urine samples. Eight schools (4 in low-risk and 4 in high-risk strata) were purposively selected. Four thick smear slides were analyzed by KK while urine samples were analyzed by POC-CCA for detection of S. mansoni. Data was entered using CommCare®® and analyzed using Stata version 14 software. The mean age of the 329 enrolled SAC was 10.6-10.7 while the median age was 10 years. Both POC-CCA and Kato-Katz were able to report a decrease in prevalence over time [2019 (KK= 29.5%, POC-CCA=70.3%) 2021(KK= 28%, CCA=475)]. Notably, only the POC-CCA was able to monitor the decrease for both high and low prevalence areas [Low-risk stratum <10% (2019= 63.0%, 2020= 42.4%, 2021=28.5%). High-Risk Stratum (>20%) (2019= 77.8%, 2021= 65.6%)]. Generally, the POC-CCA assay was more sensitive (<90%) and accurate than Kato-Katz, and concordance between the two tools was low, while in low prevalence areas, the strength of agreement between the two tools was poor (2019, K=0.0360, 2020, K=0.0449, 2021, K= 0.1872). Moderate agreement was recoded in high-risk stratum in 2021 (K= 0.5557, P<0.0001). Moreover, the frequency of false negatives and false positives reported by the POC-CCA tool was of great concern. In conclusion, the POC-CCA tool was able to monitor the decrease in prevalence of S. mansoni following annual rounds of MDA using praziquantel drug. However, it is still unclear if this tool can be utilized for monitoring schistosomiasis control programs due to reportedly higher number of false negatives/positives.
Keywords: Diagnostic Performance; Kato Katz; Care Circulating Cathodic Antigen Assays; Detection of Schistosoma Mansoni; Utility in Monitoring Preventive Chemotherapy